Graphene aerogel photocatalyst integrating three functions
By protonating Bi2MoO6, forming a strong electrostatic self-assembled Schottky junction with graphene aerogel, the problems of insufficient proton diffusion in water of traditional photocatalysts and difficulty in modifying Bi2MoO6 are solved, and the H2O2 generation rate and storage of photocatalysts are significantly improved. Energy performance.
Patent Information
- Application Number
- CN202411363629.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
The proton diffusion coefficient of traditional photocatalysts in water is low, which may be in a proton-deficient state on the surface of the photocatalyst, reducing the selectivity for H2O2 bi-electron oxygen reduction reaction. In addition, the individual modification of Bi2MoO6 is difficult to significantly improve its catalytic performance. Traditional Schott The base heterojunction interface is prone to instability under the action of external forces.
The charge state of Bi2MoO6 is changed through protonation treatment, making it negatively charged into positive charge, forming a strong electrostatic self-assembled Schottky junction with graphene oxide, and combining with graphene aerogel to form a composite material with strong interaction. Enhance the electron transfer and separation rate of the photocatalyst.
The H2O2 generation rate and selectivity of the photocatalyst are significantly improved, and the specific capacitance and cyclic stability of supercapacitors are improved in the field of energy storage, achieving efficient photocatalytic degradation and energy storage performance.
Smart Images

Figure CN119236916A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of nano material application research, in particular to the application of graphene aerogel in wastewater treatment, energy production and energy storage devices. Background Art
[0002] In recent years, photocatalytic degradation technology has developed rapidly in the treatment of water pollution due to its environmental friendliness and simple methods, showing great application potential. In addition to being able to degrade organic pollutants, photocatalysis can also be used for photocatalytic water splitting, CO2 reduction, H2O2 production, organic synthesis and other applications. Among them, since the traditional industrial manufacturing technology for producing H2O2 (anthraquinone oxidation (AO) process) consumes a lot of energy and produces a large amount of toxic by-products, photocatalytic H2O2 production has been used as an alternative to the industrial AO process and has received widespread attention on certain semiconductors. In the process of photocatalytic H2O2 production, molecular oxygen (O2) and water (H2O) are usually used as indispensable raw materials, sunlight is used as power, and semiconductor catalysts are used through the two-electron oxygen reduction reaction (ORR, O2+2e - +2H + →H2O2) not only reduces the energy dependence on unsustainable fossil fuels, but also alleviates environmental pressure and has great application prospects. However, due to the relatively low diffusion coefficient of protons in water (about 2.39×10 at 300K), -9 m 2 ·s -1 ), the photocatalyst surface may be in a proton-deficient microenvironment, resulting in poor ORR selectivity for H2O2. Therefore, in order to achieve high ORR selectivity for H2O2 photosynthesis, a proton-rich microenvironment must be created on the photocatalyst surface. In addition, in recent years, supercapacitors have attracted widespread attention as an energy storage device due to their high power density, fast charge and discharge capabilities, low maintenance costs, and long cycle life. Compared with batteries, supercapacitors can provide high gravimetric power density (up to 10 kW kg -1 ), long cycle life (300,000 cycles) and the additional advantages of low cost and environmental protection. The size of the capacitor basically depends on the electrode material, so the role of the electrode material is extremely important.
[0003] Among various bismuth-based catalysts, Bi2MoO6 is a typical aurivius phase oxide, which is composed of (Bi2O2) 2+Bi2MoO6 is a kind of perovskite-type (MoO4)2 layer stacked alternately, with oxygen atoms shared between the layers. In addition, the perfect lattice matching and strong chemical bonds between adjacent (Bi2O2) layers and (MoO4) layers can effectively adjust the electron distribution and maximize the interaction at the interface. Bi2MoO6 has been widely studied due to its suitable band gap (2.5-2.8 eV), non-toxicity, high photostability, thermal stability and potential photocatalytic applications. In addition, it is gratifying that the application of Bi2MoO6 has been extended to the field of energy storage, especially supercapacitors in recent years. Nevertheless, the photocatalytic and electrochemical performance of Bi2MoO6 alone is still subject to many limitations. It is reported that the introduction of surface oxygen vacancies is an effective way to narrow the band gap and inhibit the recombination of photogenerated carriers in semiconductors, thereby achieving high photocatalytic activity, and the oxygen vacancies in the Bi2MoO6 structure can provide an ideal place for the rapid transfer of electrons and enhance the electrochemical performance. However, the catalytic performance cannot be significantly improved by simply introducing oxygen vacancies in Bi2MoO6. Therefore, it is necessary to modify Bi2MoO6 by some other means to improve its catalytic performance by an order of magnitude. Interface engineering has been proven to be an effective strategy for regulating the performance of photocatalysts, and the formation of Mott-Schottky (MS) heterojunctions represents a unique strategy. This is mainly due to the autonomous electron transfer at the heterojunction interface, and the resulting charge redistribution is beneficial to the electron transfer reaction on the electrode surface. Mechanistically, the built-in electric field promotes the local charge polarization at the heterojunction interface, greatly improving the separation and transfer of photogenerated carriers, thereby improving the photocatalytic activity. However, the interaction force of traditional Schottky heterojunction interfaces is often weak, and it is easy to cause the two to separate under the action of external forces (such as rapid stirring), resulting in a decrease in performance. Therefore, it is necessary to construct a heterojunction interface with a strong interaction force to ensure the performance stability of the photocatalyst.
[0004] Graphene aerogel (GA) is a three-dimensional (3D) graphene material mainly generated by the reduction of graphene oxide. It is currently gaining more and more attention in energy storage and environmental applications. In addition, compared with two-dimensional graphene, the shape, volume and density of three-dimensional gas can be easily controlled by adjusting the characteristics of the reaction container, which indicates the possibility and feasibility of large-scale production. Therefore, the introduction of GA as a carrier is considered to be an effective strategy to improve the catalytic performance. The resulting composite material can form a unique Schottky junction interface and take into account the advantages of graphene aerogel. In this way, GA with rich pore structure and large specific surface area can make Bi2MoO6 nanosheets uniformly dispersed on the graphene surface, while its black body surface sensitization and high conductivity can also promote light absorption and carrier migration. However, our experimental tests found that the surfaces of graphene oxide and Bi2MoO6 are both negatively charged, which makes them connect through weak interactions when they are composited, and some of them cannot even effectively composite together to form Schottky junctions, slowing down the transfer of carriers. Here, we are inspired by the hot research on proton batteries in recent years and believe that Bi2MoO6 can be oxidized by proton acid, introducing rich surface functional groups to combine with graphene. Importantly, due to the introduction of hydrogen ions, the original negative charge of Bi2MoO6 will become positive. Therefore, we predict that protonated Bi2MoO6 can connect with graphene oxide through strong electrostatic self-assembly to form a Schottky junction, greatly accelerating the transfer and separation rate of carriers and enhancing the catalytic performance of Bi2MoO6.
[0005] In the present invention, we have successfully synthesized protonated Bi2MoO6 / GA with oxygen vacancies. After protonation, the negatively charged Bi2MoO6 becomes positively charged, and combines with graphene oxide through strong electrostatic attraction to form a Schottky heterojunction. It is expected that the graphene co-catalyst can effectively guide the photogenerated electrons to the surface, thereby promoting the effective separation and transfer of photogenerated carriers. The protonated Bi2MoO6 / GA with oxygen vacancies exhibits excellent photocatalytic degradation of tetracycline and production of H2O2. In addition, it is also applied to energy storage. Although there is no direct connection between photocatalysis and electrochemical energy storage phenomena, many properties of the materials are common. For example, both like materials with high specific surface area and high conductivity, the component interface in the composite material is conducive to charge transfer, and it is easy to enter the active sites of substrate / photon / electrolyte ions. Through the characterization of samples in the photocatalytic process, we found that many requirements for energy storage applications are very similar. Therefore, we decided to use these samples for energy storage applications as well and found that asymmetric supercapacitor devices assembled from Bi2MoO6 / GA exhibited high specific capacitance and good cycling stability. Summary of the invention
[0006] We prepared Bi2MoO6 graphene aerogels with strong interactions and oxygen vacancies by protonation. Protonation changes the initial charge state of OBMO, allowing it to generate stronger electrostatic attraction with graphene before forming aerogels. The steps are:
[0007] (1) Preparation of Bi2MoO6 (BMO) and Bi2MoO6 with O vacancies (OBMO)
[0008] Bi2MoO6 nanosheets were prepared by solvothermal method. First, 194mg Bi(NO3)3·5H2O and 48.4mg Na2MoO4·2H2O were dissolved in 5mL ethylene glycol, then the two solutions were mixed and 30mL ethanol was added and stirred for 30min. The mixed solution was transferred to a reactor and kept at 160℃ for 24h to obtain pure Bi2MoO6 nanosheets. The surface oxygen vacancies of Bi2MoO6 were generated by thermal reduction. 100mg of the prepared Bi2MoO6 was placed in a porcelain boat and heated at 300℃ for 2h under Ar atmosphere to obtain Bi2MoO6 and was labeled as OBMO.
[0009] (2) Preparation of protonated Bi2MoO6 graphene aerogel (p-OBMO / GA)
[0010] To prepare protonated OBMO, OBMO (500 mg) was slowly added to 2 mol·L -1 H2SO4 (98%) was added and stirred at room temperature for 5 h. The mixed solution was then added to 1 L of deionized water and washed to neutrality. Powdered p-OBMO was obtained by precipitation freeze drying. Graphene oxide (GO) was prepared by the improved Hummer method. 70 mg of p-OBMO was dispersed in 10 mL of GO dispersion (3.5 mg mL -1 ), ascorbic acid (GO:VC=1:2) was added and ultrasonically dispersed for 30 min, then the mixed solution was kept at 90 °C for 2 h and vacuum freeze-dried to obtain p-OBMO / GA.
[0011] A strongly interacting BMO graphene aerogel containing oxygen vacancies was prepared by protonation. The initial charge state of OBMO was changed by protonation, so that it could generate a stronger electrostatic attraction with graphene before forming aerogel. Therefore, the prepared p-OBMO / GA exhibited excellent photocatalytic performance and energy storage capacity. Through a series of experimental tests and characterizations, p-OBMO / GA can efficiently remove TC under simulated sunlight, and can effectively degrade TC even in tap water and real lake water. Similarly, under simulated sunlight, p-OBMO / GA also has 2284.2μmol h-1 g -1 In addition, the specific capacitance of p-OBMO / GA in the three-electrode system and asymmetric supercapacitor device was 840.6F·g -1 and 206.6F·g -1 , and has good cycle performance. It is believed that this protonation treatment method can provide good inspiration for the preparation of more monolithic aerogels and other materials, and this three-functional graphene aerogel has great application potential in wastewater treatment, energy production and energy storage devices, achieving the purpose of the invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 is the Zeta potential diagram of GO, OBMO and p-OBMO / GA;
[0013] Figure 2 is a SEM photo of p-OBMO / GA, which also serves as an abstract figure;
[0014] Figure 3 are the XRD patterns of BMO, OBMO, OBMO / GA and p-OBMO / GA;
[0015] Figure 4 are the N2 adsorption–desorption isotherms of BMO, OBMO, OBMO / GA, and p-OBMO / GA;
[0016] Figure 5 It is the performance diagram of photocatalytic TC removal of BMO, OBMO, OBMO / GA and p-OBMO / GA under simulated sunlight;
[0017] Figure 6 It is the performance diagram of photocatalytic H2O2 precipitation of BMO, OBMO, OBMO / GA and p-OBMO / GA under simulated sunlight;
[0018] Figure 7 are BMO, OBMO, OBMO / GA and p-OBMO / GA in 1Ag -1 The charge and discharge curves at
[0019] Figure 8 is the charge and discharge curves of the asymmetric supercapacitor assembled with p-OBMO / GA at different current densities;
[0020] Fig. 9 Schematic diagram of the trifunctional application of p-OBMO / GA. DETAILED DESCRIPTION
[0021] The purity of Na2MoO4·2H2O and Bi(NO3)3·5H2O used in the present invention is 99.99%, and they are commercially available analytically pure products; the glass instruments, crucibles and equipment used are commonly used instruments and equipment in laboratories.
[0022] Example: Zeta potential instrument was used to demonstrate the protonation of OBMO. Figure 1 It can be found that the potentials of the initial GO and OBMO are -24.05 and -19.71 mV, respectively, while the potential of the protonated OBMO is +9.73 mV, which fully proves that protonation changes the charge state of OBMO, enabling it to generate a strong electrostatic attraction with graphene when forming aerogel. The SEM photo of the prepared sample p-OBMO / GA is shown in Figure 2. Figure 2 As shown in Figure 2, when OBMO nanosheets are combined with graphene oxide to form graphene aerogel, due to the large number of functional groups on the surface of graphene oxide, it can be found that OBMO nanosheets are fixed on the surface of conductive graphene, which is conducive to accelerating the electron transfer rate. The XRD pattern of the prepared sample is shown in Figure 2. Figure 3 As shown, all samples show strong and sharp diffraction peaks. The diffraction peaks at 2θ=10.9°, 28.2°, 32.6°, 47.1° and 55.6° in the BMO sample are respectively attributed to the (020), (131), (022), (202) and (331) crystal planes of the orthorhombic phase BMO (PDF#72-1524). It can be seen from the figure that after calcination, not only O vacancies are formed in BMO but also the crystallinity of BMO is improved. The diffraction peaks of OBMO / GA and p-OBMO / GA can correspond one by one to the peaks of OBMO, which indicates that the crystal structure and phase composition of OBMO after proton acidification have not changed, and it also means the successful combination of the composite material. The BET test results of the prepared materials are shown in Figure 4 As shown, the BET area of pure BMO is smaller (33.42 m 2 g -1 ), when combined with graphene aerogel, the specific surface area of the sample increased to 104.68m 2 g -1 , proving that the introduction of aerogels gives them more active sites. The increase in BET area may be due to the strong electrostatic attraction that allows more OBMO nanosheets to be loaded on the aerogels, exposing more active sites. Figure 5As shown, the prepared samples were tested for photocatalytic degradation of tetracycline (TC) under simulated sunlight. For BMO nanosheets with and without oxygen vacancies, the photodegradation rates of TCH within 30 min were 50.1 and 43.1%, respectively. When graphene aerogel was introduced as a carrier, the degradation ability of TC was significantly enhanced under the synergistic effect of adsorption and photocatalysis. OBMO / GA can degrade 77.4% of TC within 30 min. When the graphene aerogel composed of protonated OBMO showed the best TC degradation ability, it could degrade 97.3% of TC within 30 min. We further studied the test of photocatalytic H2O2 production of the prepared samples. As Figure 6 As shown in Figure 2, the H2O2 production of pure BMO and OBMO under simulated sunlight within 120 min was 57.6 and 97.2 μmol L -1 Combined with the photocatalytic degradation TC test results, it shows that the generation of O vacancies can effectively stimulate the photogenerated charge dynamics and increase the electron lifetime as an electron trap, thus improving the photocatalytic performance. The H2O2 production of OBMO / GA within 120 min was 142.8 μmol L -1 The H2O2 yield of p-OBMO / GA after protonation was the highest, reaching 228.4 μmol L in 120 min. -1 In addition, the H2O2 precipitation rate of p-OBMO / GA was the highest, reaching 2284.2 μmol h -1 g -1 . Protonation can generate more Schottky heterogeneous interfaces between BMO and graphene to inhibit the recombination of electron holes, and the strong binding force between BMO and graphene is conducive to the generation of H2O2. The introduction of graphene aerogel can increase the electron transfer rate. The unique three-dimensional network of aerogel can provide multiple transfer pathways for electrons, which can induce more and faster photogenerated electrons and O2 - To generate H2O2. The electrodes of the prepared samples were tested for supercapacitors using a three-electrode system. Pristine BMO, OBMO, OBMO / GA and p-OBMO / GA at 1Ag -1 The charge and discharge curves are as follows Figure 7 As shown in Figure 2, all three samples are irregular triangles with tilted platforms, which are consistent with the typical characteristics of pseudocapacitors. The capacitance values of the original BMO and OBMO are 192.2 and 284.4 F·g, respectively. -1 The results show that the generation of oxygen vacancies can generate additional active sites, thereby improving the charge storage capacity of the BMO electrode. After the introduction of graphene aerogel as a carrier, the capacitance values of OBMO / GA and p-OBMO / GA increased to 460.2 and 840.6 F·g, respectively. -1, which can be attributed to the large specific surface area and good conductivity of graphene, which is conducive to the transfer of electrons. In addition, all the discharge curves are almost symmetrical with the corresponding charging curves, indicating that these electrodes have good electrochemical reversibility. The p-OBMO / GA with excellent capacitive performance was assembled into an asymmetric capacitor device for testing. Figure 8 As shown, at a current density of 1A g -1 , 2Ag -1 , 3A g -1 , 5A g -1 and 8Ag -1 The capacitance is 206.6F·g -1 、188.8F·g -1 , 153.3F·g -1 , 127.7F·g -1 and 115.5F·g -1 It can be found that the GCD curve also achieves a higher potential from 0.1 V to 1 V. The excellent conductivity, rich functional groups on the surface and high pore structure of graphene aerogel enhance the interface between the microbattery inside the electrode and the electrolyte, and the contact area is large, thereby reducing the interface transfer resistance and increasing the capacitance.
[0023] OBMO graphene aerogels with strong interactions and containing oxygen vacancies were prepared by protonation. Protonation changes the initial charge state of OBMO, allowing it to generate stronger electrostatic attraction with graphene before forming aerogels. Fig. 9 As shown, the prepared p-OBMO / GA exhibits excellent photocatalytic performance and energy storage capacity. The enhancement of the heterojunction effect by protonation treatment provides a new idea for the construction and upgrading of interface engineering. The successful integration of these three functions into one aerogel shows the great potential of this work in achieving wastewater treatment and feasible energy production methods and energy storage capabilities.
[0024] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art may make various corresponding changes and modifications based on the present invention, but these corresponding changes and modifications should all fall within the scope of protection of the claims attached to the present invention.
Claims
1. A graphene aerogel photocatalyst integrating three functions, characterized in that: Protonated Bi2MoO6 graphene aerogel containing oxygen vacancies. The volume of the graphene aerogel is about 2.35cm 3 , density is 10 mg cm -3 Under simulated sunlight, it has good photocatalytic properties for producing hydrogen peroxide and photocatalytic degradation of tetracycline hydrochloride (TC), and has high specific capacitance and good cycle stability in three-electrode systems and asymmetric supercapacitors.
2. A manufacturing technology of a graphene aerogel photocatalyst integrating three functions as claimed in claim 1, characterized in that: Bi2MoO6 graphene aerogel with strong interaction and containing oxygen vacancies was prepared by protonation. The initial charge state of Bi2MoO6 with O vacancies was changed by protonation, so that it could generate stronger electrostatic attraction with graphene before forming aerogel. The steps are as follows: (1) Preparation of Bi2MoO6 (BMO) and Bi2MoO6 with O vacancies (OBMO) Bi2MoO6 nanosheets were prepared by solvothermal method. First, 194 mg of Bi(NO3)3·5H2O and 48.4 mg of Na2MoO4·2H2O were dissolved in 5 mL of ethylene glycol, respectively. The two solutions were mixed and then 30 mL of ethanol was added and stirred for 30 min. The mixed solution was transferred to a reactor and kept at 160 °C for 24 h to obtain pure Bi2MoO6 nanosheets, named BMO. The surface oxygen vacancies of Bi2MoO6 were generated by thermal reduction. 100 mg of the prepared Bi2MoO6 was placed in a porcelain boat and heated at 300 °C for 2 h under Ar atmosphere. The obtained Bi2MoO6 was named OBMO. (2) Preparation of protonated Bi2MoO6 graphene aerogel (p-OBMO / GA) OBMO (500 mg) was slowly added into 2 mol·L -1 H2SO4 (98%) was added and stirred at room temperature for 5 h. The mixed solution was then added to 1 L of deionized water and washed to neutrality. Finally, powdered p-OBMO was obtained by precipitation freeze drying. Graphene oxide (GO) was prepared by the improved Hummer method. 70 mg of p-OBMO was dispersed in 10 mL of GO dispersion (3.5 mg mL -1 ), ascorbic acid (GO:VC=1:2) was added, and after ultrasonic dispersion for 30 min, the mixed solution was kept at 90 °C for 2 h, and then vacuum freeze-dried to obtain p-OBMO / GA; The BMO graphene aerogel with strong interactions and containing oxygen vacancies was prepared by protonation. The initial charge state of OBMO was changed by protonation, so that it could generate a stronger electrostatic attraction with graphene before forming aerogel. Therefore, the prepared p-OBMO / GA showed excellent photocatalytic performance and energy storage capacity. Through a series of experimental tests and characterizations, p-OBMO / GA can efficiently remove TC under simulated sunlight conditions, and can effectively degrade TC even in tap water and real lake water. Under simulated sunlight, p-OBMO / GA also has a photocatalytic activity of 2284.2 μmol h - 1 g -1 In addition, the specific capacitance of p-OBMO / GA in the three-electrode system and asymmetric supercapacitor device was 840.6 F·g -1 and 206.6F·g -1 , and has good cycle stability.
